2019
DOI: 10.1002/aoc.4979
|View full text |Cite
|
Sign up to set email alerts
|

Stable poly (ionic liquids) with unique cross‐linked mesoporous‐macroporous structure as efficient catalyst for alkylation of o‐xylene and styrene

Abstract: In this work, using divinylbenzene (D), 1-vinylimidazole (V) and 1-vinyl-3butylimidazolium bromide ([VBIM][Br]) as monomers, the binary-monomer poly (ionic liquids) (PILs) and ternary-monomer PILs were successfully synthesized, via hydrothermal polymerization and anion exchange, sequentially. Compared with each other, the ternary polymeric acidic IL catalyst has a clear spongy porous structure, while having a more stable macroporous structure, a larger specific surface area, more acidic groups and more active … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Compared with SiO 2 , SiO 2 @MPS showed a characteristic peak of CO stretching vibration at 1716 cm –1 , which originated from the modification of the silane coupling agent . For SiO 2 @MPS@MIPs-MFM and SiO 2 @MPS@NIPs-MFM samples, the peaks at 1456 and 1549 cm –1 were ascribed to the deformation and stretching vibration of the imidazolium ring, indicating the successful grafting polymerization of MFM. , The surface elemental composition of SiO 2 @MPS, SiO 2 @MPS@MIPs-MFM, and SiO 2 @MPS@NIPs-MFM was further determined by XPS analysis. It can be seen from Figure B that the SiO 2 @MPS microsphere contained only Si, O, and C elements, whereas both MIPs and NIPs showed new signals at 399.6, 130.6, 255.2, 69.1, 198.7, 229.1, and 164.0 eV, which were attributed to the characteristic peaks of N 1s, P 2p, Br 3s, 3d, Cl 2p, S 2s, and 2p, respectively. ,, In addition, thermogravimetric analysis (TGA) results in Figure C also showed that SiO 2 @MPS@MIPs-MFM and SiO 2 @MPS@NIPs-MFM had higher weight loss than the bare SiO 2 @MPS microsphere in the temperature range from 100 to 600 °C, which may be caused by the decomposition of the polymer layer .…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Compared with SiO 2 , SiO 2 @MPS showed a characteristic peak of CO stretching vibration at 1716 cm –1 , which originated from the modification of the silane coupling agent . For SiO 2 @MPS@MIPs-MFM and SiO 2 @MPS@NIPs-MFM samples, the peaks at 1456 and 1549 cm –1 were ascribed to the deformation and stretching vibration of the imidazolium ring, indicating the successful grafting polymerization of MFM. , The surface elemental composition of SiO 2 @MPS, SiO 2 @MPS@MIPs-MFM, and SiO 2 @MPS@NIPs-MFM was further determined by XPS analysis. It can be seen from Figure B that the SiO 2 @MPS microsphere contained only Si, O, and C elements, whereas both MIPs and NIPs showed new signals at 399.6, 130.6, 255.2, 69.1, 198.7, 229.1, and 164.0 eV, which were attributed to the characteristic peaks of N 1s, P 2p, Br 3s, 3d, Cl 2p, S 2s, and 2p, respectively. ,, In addition, thermogravimetric analysis (TGA) results in Figure C also showed that SiO 2 @MPS@MIPs-MFM and SiO 2 @MPS@NIPs-MFM had higher weight loss than the bare SiO 2 @MPS microsphere in the temperature range from 100 to 600 °C, which may be caused by the decomposition of the polymer layer .…”
Section: Resultsmentioning
confidence: 97%
“…38 For SiO 2 @MPS@MIPs-MFM and SiO 2 @MPS@NIPs-MFM samples, the peaks at 1456 and 1549 cm −1 were ascribed to the deformation and stretching vibration of the imidazolium ring, indicating the successful grafting polymerization of MFM. 30,39 The surface elemental composition of SiO 2 @MPS, SiO 2 @MPS@MIPs-MFM, and SiO 2 @MPS@NIPs-MFM was further determined by XPS analysis. It can be seen from Figure 3B to the characteristic peaks of N 1s, P 2p, Br 3s, 3d, Cl 2p, S 2s, and 2p, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The systems of this type were characterized by a greater number of acid groups and active centers on their surface than their binary analogs. Additionally, the presence of micro-and mesopores in the structure of the porous ternary polymer increased the possibility of contact between reagents, which resulted in the high conversion of substrates (99%) [117]. The high activity of porous ionic liquids as catalytic systems can be achieved not only by the formation of certain structures but also by the generation of acid-base properties.…”
Section: Methodsmentioning
confidence: 99%
“…[11][12][13][14][15] Alkylation catalyzed by acidic ILs is one of the focuses of catalysis study due to the possibility of acidity control and the unique physicochemical properties. [16][17][18][19][20][21][22][23] For example, 1-alkyl-3-methylimidazolium halidealuminum chloride ILs have been investigated as catalysts for isobutane/2-butene alkylation. [24,25] Lewis acidic chloroaluminate ILs synthesized by aluminum chloride and triethylamine hydrochloride has also been confirmed to be an excellent catalyst for alkylation.…”
Section: Introductionmentioning
confidence: 99%